Combined hamartoma of the retina and retinal pigment epithelium at pediatric age: surgical versus conservative approach - ŞAHİN, ÖZLEM (My University, 2022)
Purpose: To report outcomes of pediatric patients with combined hamartoma of the retina and the retina pigment epithelium (CHRRPE) followed up conservatively or after pars plana vitrectomy (PPV). Methods: This retrospective multicenter study included sixty-two eyes of 59 pediatric patients with CHRRPE from 13 different international centers with an average age of 7.7±4.7 (0.3-17) years at the time of the diagnosis, and having undergone PPV or followed conservatively. At baseline and each visit, visual acuity values, optical coherence tomography (OCT) for features and central foveal thickness (CFT), and tumor location were noted. Lesions were called as zone 1, if it involves the macular and peripapillary area, and the others were called as zone 2 lesions. Results: Twenty-one eyes of 20 patients in the intervention group and 41 eyes of 39 patients in the conservative group were followed for a mean of 36.2±40.4 (6-182) months. BCVA improved in 11 (68.8%) of 16 eyes in the intervention group and 4 (12.9%) of 31 eyes in the conservative group (p<0.001). The mean CFT decreased from 602.0±164.9 μm to 451.2±184.3 μm in the intervention group, while it increased from 709.5±344.2 μm to 791.0±452.1 μm in zone 1 eyes of the conservative group. Posterior location of tumor, irregular configuration of the foveal contour and ellipsoid zone defect in OCT, subretinal exudate and prominent vascular tortuosity were associated with poor visual acuity. Conclusions: Vitreoretinal surgery is safe and effective in improving vision and reducing retinal distortion in zone 1 CHRRPE in children.
Keywords: combined hamartoma of the retina and the retina pigment epithelium; pediatric age; pars plana vitrectomy; retina; retinal pigment epithelium; surgery; amblyopia treatment